PELAKSANAAN REWARD DAN PUNISHMENT DALAM MENANAMKAN NILAI-NILAI AGAMA PADA ANAK DI TAMAN KANAK-KANAK ISLAMIC CENTER SAMARINDA - Nurwati - Nurwati; Nurul - Muawwanah (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2019)
This study is entitled "The Implementation of Reward and Punishment in instilling religious values in children in the Islamic Center Kindergarten in Samarinda. In the learning process many techniques are used by teachers to achieve learning goals, one of them is using reward and punishment techniques. Kindergarten Islamic Center is one of the Islamic educational institutions that aims to produce a generation of monotheists who adhere to worship in life by introducing God through sentences thoyyibah and Asmaul Husna using Reward and Punishment techniques. So this study aims to find out how the implementation of the provision of rewards and punishments in kindergarten Islamic Center Samarinda.This research is a descriptive qualitative research that is describing the situation in Islamic Kindergarten. Informants in this study are the principal and teachers. The data collection techniques using the method of observation, interviews and documentation. For the validity of the data using data reduction, data presentation and drawing conclusions or verification. The results showed that in the implementation of rewards and punishments carried out in kindergarten Islamic Center reward and punishment is one of the teacher's techniques to develop aspects of religious values and is given to each activity in accordance with the circumstances. Rewards are given when children are able to follow the rules, children are able to complete tasks well, and children are independent and patient. Reward is given in several forms, namely the form of praise, the form of goods, forms of touch and applause. Whereas punishment is given when the child does not follow the rules, does not complete the task properly, is not being independent and patient. There are several stages of punishment given, namely giving advice, separating children from groups in a few moments and transferring children to other classes.